The Policing Mind : Developing Trauma Resilience for a New Era - Miller, Jessica K. (Book collections on Project MUSE., 2022)
How does it feel to be a police officer? Jessica Miller uses the most recent neuroscience and real-life examples to explore risks to individual resilience. A compulsory read for anyone with an interest in policing, the book offers practical resilience techniques and policy recommendations for police officers facing crime in a post-COVID world.